The Effect Of Green Life Style, Futuristic Design, Technology On Purchasing Decisions For Electric Motorbikes With Confidence As An Intervening Variable In Medan City - Syafrida Yani Harahap; Satria Tirtayasa (SEAN Institute, 2024)
The purpose of this study is to systematically analyze the influence of Green Lifestyle, Futuristic Design, and Technology on Purchasing Decisions for Electric Motorbikes in Medan City. In addition, this study aims to assess the mediating role of Confidence as an important variable in shaping the relationship. The sample size was 100 respondents selected through purposive sampling. The results showed: (1) green lifestyle has a positive and significant effect on purchasing decisions (2) futuristic design has a positive and insignificant effect on purchasing decisions. (3) technology has a positive and significant effect on purchasing decisions. (4) confidence has a positive and significant effect on purchasing decisions. (5) confidence does not play a role in mediating the relationship between Green Lifestyle, Futuristic Design and Technology on Purchasing Decisions.